2017
DOI: 10.1242/dmm.028092
|View full text |Cite
|
Sign up to set email alerts
|

Genetic mutations linked to Parkinson's disease differentially control nucleolar activity in pre-symptomatic mouse models

Abstract: Genetic mutations underlying neurodegenerative disorders impair ribosomal DNA (rDNA) transcription suggesting that nucleolar dysfunction could be a novel pathomechanism in polyglutamine diseases and in certain forms of amyotrophic lateral sclerosis/frontotemporal dementia. Here, we investigated nucleolar activity in pre-symptomatic digenic models of Parkinson's disease (PD) that model the multifactorial aetiology of this disease. To this end, we analysed a novel mouse model mildly overexpressing mutant human α… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 50 publications
2
26
0
Order By: Relevance
“…Although the presence of α‐syn in the nucleus has been controversial, recent studies have consistently found evidence of nuclear α‐syn (Ma et al, 2014; Pinho et al, 2019; Siddiqui et al, 2012; Zhou, Xu, Mi, Ueda, & Chan, 2013). In mice overexpressing human A53T α‐syn in a PINK1 null background, mutant α‐syn was also reported to be in the nucleus (Evsyukov et al, 2017). Nuclear α‐syn can bind DNA and when overexpressed can cause DNA single‐strand breaks and double‐strand breaks, particularly under oxidative conditions (Vasquez et al, 2017).…”
Section: Dna Damage Response and Dna Double‐strand Break Repair In Pdmentioning
confidence: 99%
“…Although the presence of α‐syn in the nucleus has been controversial, recent studies have consistently found evidence of nuclear α‐syn (Ma et al, 2014; Pinho et al, 2019; Siddiqui et al, 2012; Zhou, Xu, Mi, Ueda, & Chan, 2013). In mice overexpressing human A53T α‐syn in a PINK1 null background, mutant α‐syn was also reported to be in the nucleus (Evsyukov et al, 2017). Nuclear α‐syn can bind DNA and when overexpressed can cause DNA single‐strand breaks and double‐strand breaks, particularly under oxidative conditions (Vasquez et al, 2017).…”
Section: Dna Damage Response and Dna Double‐strand Break Repair In Pdmentioning
confidence: 99%
“…The mice exhibited progressive degeneration of dopaminergic neurons, reduced striatal dopamine levels, and behavioral abnormalities (Rieker et al., ). In contrast to PD patients and toxin‐induced mouse PD models, nucleolar integrity was not affected by DJ‐1/PINK1 double knockout, highlighting the value of the TIF‐IA conditional knockout model to study PD‐related nucleolar dysfunction (Evsyukov et al., ). The utility of TIF‐IA/DAT‐CreET2 mice for pre‐clinical drug testing has recently been proven by the study showing a neuroprotective effect of reboxetine, a selective noradrenaline reuptake inhibitor, on dopaminergic neurons (Kreiner et al., ).…”
Section: Genetic Modelsmentioning
confidence: 99%
“…High levels of nucleolar activity are a hallmark of cancer and contribute to tumor growth by allowing de-regulated protein synthesis and uncontrolled activity of nucleolar cell growth/death pathways [ 16 , 82 ]. Changes in nucleolar morphology and function are also common in age related neurodegenerative disorders and increasing evidence suggests that this dysfunction contributes to disease progression, as well as the normal aging process [ 17 , 18 , 46 , 83 , 84 ]. Similarly, dysregulated NF-κB activity is common in cancer, neurodegenerative disorders and aging and contributes to the progression of these diseases/aging through promotion of a chronic inflammatory environment and modulation of genes that regulate cell growth/death [ 40 , 85 , 86 ].…”
Section: Therapeutic Relevance Of Crosstalk Between Nucleoli and Tmentioning
confidence: 99%